(Invited) Thermal Carbonization of Porous Silicon: The Current Status and Recent Applications. (18th September 2015) - Salonen, Jarno; Kaasalainen, Martti; Rauhala, Olli-Pekka; Lassila, Lippo; Hakamies, Martta; Jalkanen, Tero; Hahn, Robert; Schmuki, P.; Mäkilä, Ermei
Abstract : The current status and recent new applications of thermally carbonized porous silicon (TCPSi) are discussed in this paper. The basic physicochemical properties of TCPSi, relevant to the applications, are also described and new information related to mechanical, electrical and optical properties of TCPSi is introduced. Also, the further functionalization of thermally carbonized PSi is described.